Pengaruh Penyuluhan Gizi Tentang Pemberian Tablet Zat Besi Kepada Ibu Hamil Terhadap Pengetahuan Dan Sikap Kader Posyandu Di Danau Paris Kabupaten Aceh Singkil Tahun 2009 - Siagian, Albiner; Lubis, Zulhaida; Munthe, Yanti Yanda (Pergizi Pangan DPD NTT, 2009)
According to the Household Health Survey (SKRT) 2001, nationally, the prevalence of anemia in pregnant women is still high (40.9%). One of the ways chosen to prevent anemia in pregnant women is by consuming iron tablets. Iron tablet administration program in Aceh Singkil is not successful yet because of several factors One of them is the less of extension given by the nutritionist to the local cadres. The purpose of this quasi-experimental study is to analyze the effect of the nutritional extension of iron tablet administration to pregnant women on knowledge and attitude of cadres of posyandu at Danau Paris, Aceh Singkil District. The population of this study was all of the 66 cadres of posyandu (integrated service post) in Danau Paris Sub-district, Aceh Singkil District. The result of paired sample t-test shows that the average total score of the respondent's knowledge before the extension was 22.17 (p<0.05). Meanwhile, the average total score of the respondents’ attitude before the extension was 13.11 and after the extension was 15.67 (p<0.05). It can be concluded that there is a significant difference between knowledge and attitude of cadres regarding iron administration and iron benefit to pregnant women before and after extension.